Solve rational equation
Please Draw Steps, and show answer please!
2 answers:
Answer:
![x=\frac{2}{5}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B2%7D%7B5%7D)
Step-by-step explanation:
![\frac{2 x}{x+2}-\frac{x}{x-1}=1](https://tex.z-dn.net/?f=%5Cfrac%7B2%20x%7D%7Bx%2B2%7D-%5Cfrac%7Bx%7D%7Bx-1%7D%3D1)
![\begin{aligned} & \Leftrightarrow \frac{2 x(x-1)}{(x+2)(x-1)}-\frac{x(x+2)}{(x-1)(x+2)}=1 \\& \Leftrightarrow \frac{2 x^{2}-2 x}{(x+2)(x-1)}-\frac{\left(x^{2}+2 x\right)}{(x+2)(x-1)}=1 \\& \Leftrightarrow \frac{2 x^{2}-2 x-\left(x^{2}+2 x\right)}{(x+2)(x-1)}=1 \\& \Leftrightarrow \frac{2 x^{2}-2 x-x^{2}-2 x}{(x+2)(x-1)}=1 \\& \Leftrightarrow \frac{x^{2}-4 x}{(x+2)(x-1)}=1 \\\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%20%26%20%5CLeftrightarrow%20%5Cfrac%7B2%20x%28x-1%29%7D%7B%28x%2B2%29%28x-1%29%7D-%5Cfrac%7Bx%28x%2B2%29%7D%7B%28x-1%29%28x%2B2%29%7D%3D1%20%5C%5C%26%20%5CLeftrightarrow%20%5Cfrac%7B2%20x%5E%7B2%7D-2%20x%7D%7B%28x%2B2%29%28x-1%29%7D-%5Cfrac%7B%5Cleft%28x%5E%7B2%7D%2B2%20x%5Cright%29%7D%7B%28x%2B2%29%28x-1%29%7D%3D1%20%5C%5C%26%20%5CLeftrightarrow%20%5Cfrac%7B2%20x%5E%7B2%7D-2%20x-%5Cleft%28x%5E%7B2%7D%2B2%20x%5Cright%29%7D%7B%28x%2B2%29%28x-1%29%7D%3D1%20%5C%5C%26%20%5CLeftrightarrow%20%5Cfrac%7B2%20x%5E%7B2%7D-2%20x-x%5E%7B2%7D-2%20x%7D%7B%28x%2B2%29%28x-1%29%7D%3D1%20%5C%5C%26%20%5CLeftrightarrow%20%5Cfrac%7Bx%5E%7B2%7D-4%20x%7D%7B%28x%2B2%29%28x-1%29%7D%3D1%20%5C%5C%5Cend%7Baligned%7D)
![\begin{aligned}& \Leftrightarrow x^{2}-4 x=(x+2)(x-1) \\& \Leftrightarrow x^{2}-4 x=x^{2}-x+2 x-2 \\& \Leftrightarrow x^{2}-4 x=x^{2}+x-2 \\& \Leftrightarrow-4 x=x-2 \\& \Leftrightarrow 5 x=2\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%26%20%5CLeftrightarrow%20x%5E%7B2%7D-4%20x%3D%28x%2B2%29%28x-1%29%20%5C%5C%26%20%5CLeftrightarrow%20x%5E%7B2%7D-4%20x%3Dx%5E%7B2%7D-x%2B2%20x-2%20%5C%5C%26%20%5CLeftrightarrow%20x%5E%7B2%7D-4%20x%3Dx%5E%7B2%7D%2Bx-2%20%5C%5C%26%20%5CLeftrightarrow-4%20x%3Dx-2%20%5C%5C%26%20%5CLeftrightarrow%205%20x%3D2%5Cend%7Baligned%7D)
therefore,
![x=\frac{2}{5}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B2%7D%7B5%7D)
<h3>
![\frac{2x}{x + 2} - \frac{x}{ - 1} = 1](https://tex.z-dn.net/?f=%20%5Cfrac%7B2x%7D%7Bx%20%2B%202%7D%20%20-%20%20%5Cfrac%7Bx%7D%7B%20-%201%7D%20%20%3D%201)
</h3>
<h3>
![⇢ \frac{2x}{x + 2} = 1 + \frac{x}{x - 1}](https://tex.z-dn.net/?f=%E2%87%A2%20%5Cfrac%7B2x%7D%7Bx%20%2B%202%7D%20%20%3D%201%20%2B%20%20%5Cfrac%7Bx%7D%7Bx%20-%201%7D%20)
</h3>
<h3>
![⇢ \frac{2x}{x + 2} = \frac{(x - 1) + x}{ - 1}](https://tex.z-dn.net/?f=%E2%87%A2%20%5Cfrac%7B2x%7D%7Bx%20%2B%202%7D%20%20%3D%20%20%5Cfrac%7B%28x%20-%201%29%20%2B%20x%7D%7B%20-%201%7D%20)
</h3>
<h3>
![⇢\frac{2x}{x + 2} = \frac{2x - 1}{x - 1}](https://tex.z-dn.net/?f=%20%E2%87%A2%5Cfrac%7B2x%7D%7Bx%20%2B%202%7D%20%20%3D%20%20%5Cfrac%7B2x%20-%201%7D%7Bx%20-%201%7D%20)
</h3>
By, Cross multiplying, we get
![⇢2x(x - 1) = (2x - 1)(x + 2)](https://tex.z-dn.net/?f=%E2%87%A22x%28x%20-%201%29%20%3D%20%282x%20-%201%29%28x%20%2B%202%29)
![⇢2 {x}^{2} - 2x = 2x(x + 2) - 1( x+ 2)](https://tex.z-dn.net/?f=%E2%87%A22%20%7Bx%7D%5E%7B2%7D%20%20-%202x%20%3D%202x%28x%20%2B%202%29%20-%201%28%20x%2B%202%29)
![⇢2 {x}^{2} - 2x = 2 {x}^{2} + 4x - x - 2](https://tex.z-dn.net/?f=%E2%87%A22%20%7Bx%7D%5E%7B2%7D%20%20-%202x%20%3D%202%20%7Bx%7D%5E%7B2%7D%20%20%20%2B%204x%20-%20x%20-%202)
Here,
from both sides will get cancelled
![⇢- 2x = 3x - 2](https://tex.z-dn.net/?f=%20%E2%87%A2-%202x%20%20%3D%203x%20-%202)
![⇢ - 2x - 3x = - 2](https://tex.z-dn.net/?f=%E2%87%A2%20-%202x%20-%203x%20%3D%20%20-%202)
![⇢- 5x = - 2](https://tex.z-dn.net/?f=%20%E2%87%A2-%205x%20%3D%20%20-%202)
![⇢x = \frac{ - 2}{ - 5}](https://tex.z-dn.net/?f=%20%E2%87%A2x%20%3D%20%20%20%5Cfrac%7B%20-%202%7D%7B%20-%205%7D%20)
![⇢ \underline { \boxed{ x = \frac{2}{5} }}](https://tex.z-dn.net/?f=%20%E2%87%A2%20%5Cunderline%20%7B%20%5Cboxed%7B%20x%20%3D%20%20%5Cfrac%7B2%7D%7B5%7D%20%7D%7D%20)
You might be interested in
5/18+7/12
=10/36+21/36
=31/36
1) The last one is correct.
Answer:
74.25.
Step-by-step explanation:
explanation.,,,,,,,,,
I only know 17 which it should be D
Answer:
A
Step-by-step explanation: